Implementation of Zoo Management Strategies for Animal Welfare in Indonesia - Arba, Risqi Mutia; Novarino, Wilson; Rizaldi, Rizaldi (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2023)
A zoo is a place to live or collect wild animals outside their natural habitat which can be controlled by the government or non-government, and functions as a breeding ground so that natural genetics is maintained. Apart from being a place of conservation, it is also a place of education and a place of recreation. The problem with zoos in Indonesia is that their management is not by the principles of animal welfare. This study aims to summarize the results of the Systematic Literature Review (SLR) by collecting reference articles related to the keyword